2015
DOI: 10.3906/sag-1402-48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of children presenting to the emergency room after electrical injury

Abstract: We retrospectively reviewed the medical records of the patients who presented to the Pediatrics Emergency Department in our hospital between May 2010 and May 2013 after sustaining an EI. The patients' data were investigated, including age, sex, location and form of exposure to electrical current, seasonal distribution, length Background/aim: To evaluate children who presented to the Pediatric Emergency Department with electrical injury and to discuss the follow-up of these cases and potential precautions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Mean age in pediatric electrical injury studies is between 5.9 and 10.1 years . In the present study, mean age was 6.8 years, similar to the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Mean age in pediatric electrical injury studies is between 5.9 and 10.1 years . In the present study, mean age was 6.8 years, similar to the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Scalds emerged as a prominent cause of pediatric burn injuries, with numerous studies, including those by Rawlins et al and Yilmaz et al, reporting them as the leading etiology [ 6 , 23 ]. Contact burns, electrical burns, flame-related injuries, and other specific causes such as fireworks or chemical agents were also identified.…”
Section: Reviewmentioning
confidence: 99%
“…Battle et al recognized commonalities in burn occurrences, mainly in 1-2-year-olds due to hot liquids and household devices [ 22 ]. Yilmaz et al found electric shocks were more common in males across all age groups [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to high-voltage electrical current, in particular, can result in death due to cardiac arrhythmias and respiratory muscle paralysis. These are very severe injuries, amplified by progressive tissue necrosis [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%